PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS V SDN SERTAJAYA 05 - Neng Ernawati; Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student learning outcomes can occur due to a lack of learning media used to facilitate students in learning. This research aims to develop puzzle media to improve the learning outcomes of elementary school students in class V. The research used is Research and Development (R&D). The results show that the puzzle media was declared "Very Valid" for testing as evidenced by the results of the media validator who obtained a media percentage of 98%, material 88%, and language 94%. The teacher response results showed a percentage of 96% and student responses showed a percentage of 90%. Meanwhile, to test the effectiveness of media in improving learning outcomes, tests were carried out in the form of pre-test and post-test and analyzed using the N-gain formula of 0.839 which is included in the high category. So it can be stated that puzzle learning media is effectively used in the classroom learning process.